Educação e Federalismo no Brasil - Gonçalves, Renaldo Antonio (2006)
Education in Brazil is recognized as essential for the country s development, and the Constitution is providing it with plentiful resources. However, the public policies of this segment are ineffective and do not manage to assist every individual in school age. One of the causes for the exclusion is the federative structure, which interferes directly with the organization of the offer of educational services. Such difficulty in assisting children in school age at public schools is distributed unequally across the federation states. The relative federative autonomy given to each level of power to manage its own school system has been producing, almost as a rule, very bad results for the entire country, but such problem is focused to a larger degree on the subgovernments of the Northeastern and Northern regions, on rural regions, and, finally, on the black and mulatto population with income of up to one minimum wage. An approach to this education/federalism relation, treating it only as a specific product of the Brazilian federalist structure would restrict the research to a mere descriptive vision with reduced explanatory capacity. Therefore, and in order to provide subsidies for the understanding of the Brazilian federalism and the offer of educational services by the State, we have chosen to compare our federative organization with that of other countries. Although the compared empirical studies of federative systems operate with difficulties to gather relevant information, to establish comparison standards and to validate the parameters chosen, such analyses are important to disclose the different shapes of the institutions developed in each country. I n this sense, the Brazilian federalism will be analyzed on a comparative basis with the North American and the German one. In order to provide grounds for the comparison, we have researched the bibliography available, the data sources contained in public websites and have deepened the analysis concerning the countries selected by means of interviews made with experts in education and federalism. In this work, we have tried to determine the similarities existing in each federative system, as well as the differential aspects in order to deepen the comparisons and thereby point out the disjunctions. We have distanced ourselves from the traditional line that discusses the centralization x decentralization dichotomy as a central focus. We have used the institutional economics theory because it seems the most adequate one to investigate the political, economic (in the sense of operating the public finances) and administrative institutions, in addition to the educational structure of each of the nations chosen. The core idea is that the structure for the offer of educational services in each country is the product of the federalist pact forged in each nation, since such pact is also responsible for organizing the political, tax and administrative structures. In this perspective, the centralization or decentralization is only the result of the organizational design produced by the institutions. To evaluate the education question in Brazil, we have used the mathematical model n-Euclidean space as a tool for measuring differences existing between education systems of the federation states and the federal district. The reading of the educational performance through this tool has allowed us to develop a numerical taxonomy to classify distances and thereby to analyze the performance differences in each subgovernment. We have used indicators of the educational system s financial and result performance related to the 1990 and 2000 IBGE (Brazilian Institute of Geography and Statistics) censuses, and researchers of the subject have surveyed data to feed the mathematical model. By using this resource, it was possible to measure the evolution of the education sector over a decade and the performance differences that each subgovernment has produced. From the analysis of the literature, comparison between federalisms and treatment given to the education segment indicators, some results were achieved that explain the changes that have taken place in the offer of educational goods and services in Brazil, such as: the tendency to reduce the differences between the education systems of each subgovernment and the importance of the federative disjunctions as obstacles to the improvement of the education offer. Thus, for the Brazilian education system to be able to advance in a democratic perspective that will enhance the population s school education, it will be necessary to design a new shape for financing the public education. This new shape should not depend on the richness of the region, state or city where the individual lives, but on an effective management of the total resources the country has available to apply in such function. I n this sense, the conclusions of this research point indicatively to the need of breaking up with the current management model and looking for a new federative arrangement that allows such advance.